A Study of Irrigation Management issues: Evidence from Uttar Pradesh and Uttarakhand - Sharma, Hari Prapan (International Journal of Psychosocial Rehabilitation, 2020)
Every economy strives to achieve an increasing growth rate. For this the usual path suggested by experts is a gradual shift from the primary sector to secondary and finally to the tertiary sector. Primary sector of the economy encompasses areas like agriculture, forestry, fishing etc. that make extensive use of the natural resources. On the other hand, the secondary sector produces the manufactured goods and the tertiary sector provides the services. The secondary and the tertiary sector however depend heavily upon the primary sector for their subsistence. India has its core competency in the primary sector so in the author’s opinion developing and strengthening the agricultural sector will help India attain the desired growth rate. Undivided Uttar Pradesh being the most populous state of the country and ranking third in terms of size is expected to contribute the maximum towards the above mentioned objective. Hence this paper makes an honest attempt to identify the trends of irrigated area in the state, find out the variance and then probe into the reasons of such variance. Finally, we recommend some measures which to our mind if implemented would go a long way to minimize the gap between the projected and actual land under irrigation. This work would be of interest of policy makers, researchers, students beside others having general inclination towards water management measures.